Principal's Strategy to Improve Teacher Performance at SMAN 2 Klari School - Rizky Aviatin; Sofyan Sauri; Eviana Hikamudin (Proceeding of International Conference on Education, Language, Literacies, and Literary Studies (ICONELS), 2024)
Teacher performance is the performance of teachers in carrying out their duties and functions by displaying work achievements in accordance with their competencies and carried out responsibly for students to realize towards the intended success. The purpose of this study was to find out how the coaching strategy of the principal to improve teacher performance in high school 2 klari. The function of this study is to obtain knowledge about principals' coaching strategies to improve teacher performance. The writing of this article uses literature studies and observations as research references. Hopefully this article will be a reference for readers and educators in conducting research, especially in the section on principal coaching strategies to improve teacher performance in schools.